Digital Evidence and the U.S. Criminal Justice System Identifying Technology and Other Needs to More Effectively Acquire and Utilize Digital Evidence - Goodison, Sean E. (RAND Corporation, 2015)
With digital devices becoming ubiquitous, digital evidence is increasingly important to the investigation and prosecution of many types of crimes. This report describes results of a research effort to identify and prioritize criminal justice needs related to digital evidence collection, management, analysis, and use.